2004
DOI: 10.2337/diacare.27.2.468
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anticoagulant Effects of Pravastatin in Patients With Type 2 Diabetes

Abstract: OBJECTIVE -Type 2 diabetes is associated with increased plasma concentrations of coagulation and inflammation markers. Different studies have shown that treatment with hydroxymethylglutaryl-CoA reductase inhibitors (statins) is associated with antithrombotic and antiinflammatory effects in addition to a cholesterol-lowering effect. Our objective was to evaluate the effect of pravastatin (40 mg/day) on coagulation and inflammation markers in type 2 diabetic patients. RESEARCH DESIGN AND METHODS -This was an ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 27 publications
2
27
1
1
Order By: Relevance
“…Statins diminish procoagulant activity, which is observed at various stages of the coagulation cascade (25). In some studies that were performed in patients who were on peritoneal dialysis, statins reduced fibrinogen levels and altered the levels and activities of t-PA and PAI-1 (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Statins diminish procoagulant activity, which is observed at various stages of the coagulation cascade (25). In some studies that were performed in patients who were on peritoneal dialysis, statins reduced fibrinogen levels and altered the levels and activities of t-PA and PAI-1 (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we aimed to evaluate the effects of pitavastatin on serum lipids as well as on serum hsCRP levels in Japanese patients with type 2 diabetes mellitus accompanied by elevated serum LDL-C, which has not yet been proved. Our study patients showed much lower hsCRP levels than subjects in most studies conducted in western countries 27,29,30) .…”
mentioning
confidence: 78%
“…Studies of the effects of statins on circulating hsCRP in type 2 diabetes have not shown consistent results [27][28][29][30] . BMI is known as a major independent determinant of hsCRP [11][12][13][14][15][16]32) and our study also showed that BMI was closely related to serum hsCRP levels in Japanese type 2 diabetic patients, although the mean BMI of our patients was 24.4 kg/m 2 , much lower than that in most studies conducted in western countries 27,29,30) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations